Creating Alternative Worlds: How Play Produces Queer Times and Spaces in Dungeons & Dragons - Wistow, Hollie (2023)
This dissertation removes queerness from strict identity practices to look at how spaces and times can be queered during moments and movements when players interacted with the fantasy role playing game Dungeons & Dragons. I conducted 7 semi-structured interviews with avid players of Dungeons & Dragons to investigate their relationships with play, time, and space. Throughout the dissertation I employ and build on the work of prominent queer scholars of time and space to create my own framework of queer space/time analysed in the context of play. I found numerous routes to queerness including, counter affective feelings in boredom, extreme success, player modifications, wandering of ‘course’ and boredom. These routes are united by their argument that individuals’ expressions and interactions with their play practices can create alternative locations, feelings, and desires - crafting queer worlds and inverting normativity.